Flight activity in pallid swifts Apus pallidus during the non‐breeding period. (11th February 2019) - Hedenström, Anders; Norevik, Gabriel; Boano, Giovanni; Andersson, Arne; Bäckman, Johan; Åkesson, Susanne
Abstract : Flight activity recorders have recently confirmed that alpine and common swifts spend the majority of their non‐breeding period on the wing, which may last 6–10 months. Here we test the hypothesis that the closely related pallid swift, a species with a breeding distribution around the Mediterranean, lead a similar aerial life‐style during its migration and wintering periods. The pallid swift usually lays two clutches in one season and therefore spends more time in the breeding area than the common swift. We successfully tracked four pallid swifts with data loggers that record light for geolocation and acceleration every 5 min to monitor flight activity. The birds wintered south of the Sahel in west Africa from the Ivory Coast to Cameroon. The pallid swifts spent the majority of their non‐breeding time in flight, especially the first two months after leaving the breeding area in autumn, while a few landing events occurred during the winter. The total time grounded was < 1%, similar to that of the common and alpine swifts. The mass specific flight metabolic rate of swifts is similar to the average non‐breeding metabolic rate of a long distance terrestrial migrant, suggesting swifts are not more likely to procure oxidative damage as a consequence of continuous flight than other migrants. The open airspace used by swifts may provide a relatively safe habitat that explain the high survival rate found in swifts.